Increasing Understanding of Research and Community Service Methods Through Webinars - Iswadi, Iswadi; Anom, Erman; Tamzil, Fachmi (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background: Insight and activeness to carry out research are things that must be owned by many people, organizations, as well as agencies and institutions, if they want conditions changes to occur in the environment that they want. Research helps to produce better changes with various methods or approaches. The college as the birthplace of reliable researches must be able the entire academic community in it to have insight into research methodology in order to increase community service. Contribution: This research was conducted to explain the implementation of webinar in order to increase the understanding and mastery of the academic community from lectures, students, and the public in general regarding research methodology. Method: The methodology used is qualitative descriptive. Results: The results showed that the holding of the webinar activity "Research Methodology and Scientific Writing" by the Faculty of Communication Sciences, Esa Unggul University, Jakarta had an impact on increasing the participants' insight and understanding regarding research methodology for students and other general participants. In addition, this activity also helps to encourage an increase in the interest of the academic community both from the Faculty of Communication Sciences and not to do community service with a variety of research method approaches needed by field conditions and integration in accordance with communication science. Conclusion: “Research Methodology and Scientific Writing” by the Faculty of Sciences Communication, Esa Unggu University, had a positive impact for researcher